If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c(2c + -5) = 0 Reorder the terms: c(-5 + 2c) = 0 (-5 * c + 2c * c) = 0 (-5c + 2c2) = 0 Solving -5c + 2c2 = 0 Solving for variable 'c'. Factor out the Greatest Common Factor (GCF), 'c'. c(-5 + 2c) = 0Subproblem 1
Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0Subproblem 2
Set the factor '(-5 + 2c)' equal to zero and attempt to solve: Simplifying -5 + 2c = 0 Solving -5 + 2c = 0 Move all terms containing c to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2c = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 2c = 0 + 5 2c = 0 + 5 Combine like terms: 0 + 5 = 5 2c = 5 Divide each side by '2'. c = 2.5 Simplifying c = 2.5Solution
c = {0, 2.5}
| x+2x=128 | | 2x^2+3x=135 | | 18+x=-5-12 | | z^2+16i=0 | | 500x+1500=12000 | | 5x^2-3x-15=10 | | 3-0.5c=1.2 | | 4x^2-27x+31=-2x+6 | | 3y-23-7y+32= | | -6n-30=-2n+4-3n | | 8(x+1)-(x-7)-5(x+1)=0 | | -12x+4(x-4)=16 | | 18-(2m+8)=2+3m-17 | | 1x+3x=6 | | (k-4)= | | 5(x-1)+3=3x+2(-2+x) | | 4x^4-65x^2=-64 | | 5x-3=x-17 | | x+29x=159 | | 3(3x+8)=-6 | | -(57/20)=(7/5)a+(1/2)a | | x+20x=70 | | -13.743=1.41a-6.5a | | y=x^2-8x-33 | | 15x^2+23x+10=0 | | 5=r+(17/3)+(1/3) | | 6x+1y=67 | | 0.2(x-25.5)+.3=-.2(x-16) | | 92-(4x+11)=4(x+9)+x | | 21.12=5.5p-5.4+7.6 | | (5w-5g)(5w+4g)= | | 36+-17+-11= |